Digital finance, a booster for Indian economy during Covid-19 - Shalu Kumari (Publication Division of International Ecsis Association, 2022)
An efficient financial system is a prerequisite for a country’s economic growth and development. Financial capability is a key factor to stabilizing and functioning the financial markets. It acts as a building block for the mobilization of saving and allocating them to the productive resources. The government of India along Reserve Bank of India (RBI) have taken a number of policy initiatives to include the large unbanked masses into the financial mainstreams. Recent development in communication and technology can be used in a very efficient manner for bringing the financially excluded people under the ambit of digital financial inclusion in a cost effective manner. The purpose of this paper is to examine the role of digital finance in bringing about financial inclusion among people and how it became economic booster for the nation and citizen in the times of COVID-19. The study collects various reports published by RBI and other financial and nonfinancial institutions as relevant inputs. This research uses thematic analysis with a qualitative approach. This paper finds that Digital financial services have a great capacity to support financial inclusion for inclusive economic development. Especially in the times of COVID19, digital financial services was great help for mankind to its survival. COVID 19 was the situation when there was complete lockdown all over the nation .lockdown was necessary to save life of people and digital finance acted as a booster for any of the economies around the world.